2014
DOI: 10.1108/oir-11-2013-0261
|View full text |Cite
|
Sign up to set email alerts
|

Social media application in digital libraries

Abstract: Purpose – The purpose of this paper is to investigate the applications of social media in digital libraries and identify related problems. Design/methodology/approach – A total of ten institutions were selected from the following cultural institution types – public libraries, academic libraries, museums, government, and international organisations – to represent a variety of digital libraries developed or sponsored by different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 22 publications
(19 reference statements)
2
33
0
1
Order By: Relevance
“…Although the findings showed a low usage of social media in the academic libraries, the respondents indicated the importance of such tools and their preference for using Twitter, followed by Instagram, Facebook and YouTube. This finding corresponded with Yi et al (2013), Ramsey and Vecchione (2014), Stvilia and Gibradze (2014), Xie and Stevenson (2014) and Al-Daihani and AlAwadhi (2015) that Twitter was one of the most popular social media platforms for library marketing and engagement as it was seen as valuable in connecting the library with users and the community to share information, promote services and events, and reach users and non-users (Forrestal, 2010), thereby achieving the study's first objective.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Although the findings showed a low usage of social media in the academic libraries, the respondents indicated the importance of such tools and their preference for using Twitter, followed by Instagram, Facebook and YouTube. This finding corresponded with Yi et al (2013), Ramsey and Vecchione (2014), Stvilia and Gibradze (2014), Xie and Stevenson (2014) and Al-Daihani and AlAwadhi (2015) that Twitter was one of the most popular social media platforms for library marketing and engagement as it was seen as valuable in connecting the library with users and the community to share information, promote services and events, and reach users and non-users (Forrestal, 2010), thereby achieving the study's first objective.…”
Section: Discussionsupporting
confidence: 71%
“…Siddike et al (2015) investigated the perceptions of academic librarians toward the use of word-of-mouth (WOM) through social networking sites in marketing library services, and found that librarians had positive perceptions about the use of WOM as a marketing tool to promote library services, create awareness and build relationships with customers through social networking sites, and Facebook in particular. Twitter has been found to be the most popular social media platform for library marketing and engagement (Yi et al, 2013;Ramsey and Vecchione, 2014;Stvilia and Gibradze, 2014;Xie and Stevenson, 2014;Al-Daihani and AlAwadhi, 2015). Stvilia and Gibradze (2014) confirmed that most academic library tweets were related to building and maintaining connections with library users and informing library users about news, events, workshops, exhibitions and facilities and to promote the library collections and services.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…“Twitter was becoming an important communication tool among certain groups we [CDL] serve … Twitter appeared to offer an opportunity to get CDL's news and ideas out to a wider audience” (Starr, , p. 24). Xie & Stevenson () investigated the types of social media applications including Twitter in DLs, and further characterizes their placements, update frequency, types of interactions between digital librarians and users, various types of roles they played as well as related problems.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…meanings) content, active participation, interconnection, interrelation and all meanings concerning human beings negotiations. (Xie, Iris, Stevenson, 2014). The best public, business types of the medianetwork examples are fast integrated to the virtual world such as Facebook, Twitter, Linkedin and other online systems.…”
Section: Interdisciplinary Approach To Economics and Sociologymentioning
confidence: 99%